Study updating the ISO 9001 standard in a capital goods company (Research, Society and Development, 2020)
This article aims to identify changes to the ISO 9001 standard in its new version in 2015, compared to the old version in 2008. In addition to indicating the steps required to implement the changes in an existing Quality Management System in a production plant. industrial equipment, which does not develop the design of the equipment it manufactures. The methodology used for the development of this work was the study of ISO 9001: 2008 and ISO 9001: 2015 standards and critical analysis of an existing quality management system. Based on the evaluations of the new requirements of the standard and the condition of the current system, the necessary steps were defined to carry out the adequacy of the system and presented a basic schedule that identifies the activities and the minimum duration to be performed.